Methylation and demethylation reactions of guanine nucleotide-binding proteins of retinal rod outer segments. - Pérez-Sala, D (1991)
Retinal transducin was previously shown to be farnesylated on its gamma subunit. This farnesylation reaction on a cysteine residue near the carboxyl terminus is followed by peptidase cleavage at the cysteine. Thus the modified cysteine becomes the carboxyl terminus. It is shown here that the free carboxyl group can be methylated by an S-adenosyl-L-methionine-dependent methyltransferase associated with the rod outer segment membranes. This process can be inhibited by S-adenosyl-L-homocysteine and sinefungin. Moreover, synthetic N-acetyl-S-farnesyl-L-cysteine, but not N-acetyl-L-cysteine, is a substrate for the enzyme. Rapid demethylation of N-acetyl-S-farnesyl-L-cysteine methyl ester can be observed in the membranes. Transducin is also enzymatically demethylated by the rod outer segment membranes. Moreover, the 23- to 29-kDa small G proteins are methylated and demethylated in this system. These data suggest that methylation/demethylation may play a regulatory role in visual signal transduction.